(untitled) (Research, Society and Development, 2021)
This article aims to understand and discuss how care in a medical and adolescent health team occurs, in the perceptions of professionals who are dedicated to this form of action. The method used was descriptive research, with a qualitative approach, with the participation of 25 professionals working in five medical and adolescent health teams in Brazil. We conducted a semi-structured interview with each participant, using participant observation. Data were organized and analyzed through thematic analysis, from which two categories stand out: Adolescent health care and Daily challenges for medical and adolescent health teams. We find professionals who are highly prepared to provide differentiated assistance to teenagers across all age groups. Numerous structural challenges related to team building were presented, from the extension of intersectoral care to the need for collaborative and training work, which promote reciprocal exchanges between health professionals and school staff and, therefore, reverberate in the expansion, quality and access of adolescents to services suitable for their age group. With regard to the training of professionals, issues of communication, theoretical and practical, historical and cultural context. We conclude that, despite the existence of many challenges for the performance of these professionals, they realize that there is a need for public policies that enforce the guarantees of rights and there is a permanent effort to overcome these challenges.